2020
DOI: 10.1002/jssc.201901013
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics study of different parts of licorice from different geographical origins and their anti‐inflammatory activities

Abstract: Glycyrrhiza uralensis Fisch., known as licorice, is one of the most famous traditional Chinese medicines. In this study, we perform a metabolome analysis using liquid chromatography-tandem mass spectrometry to assign bioactive components in different parts of licorice from different geographical origins in Gansu province of China. Sixteen potential biomarkers of taproots from different geographical origins were annotated, such as glycycoumarin, gancaonin Z, licoricone, and dihydroxy kanzonol H mainly exist in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…In this study, the overall chemical profile of G. uralensis in terms of the types and contents is in agreement to previous studies ( Bai et al, 2020 ; Kitagawa et al, 1993 ; Song et al, 2017 ; Yu et al, 2021 ). The roots and aerial parts showed the presence of varying abundance of different classes of phytochemicals such as total phenolics, flavonoids, tannins, and saccharides.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the overall chemical profile of G. uralensis in terms of the types and contents is in agreement to previous studies ( Bai et al, 2020 ; Kitagawa et al, 1993 ; Song et al, 2017 ; Yu et al, 2021 ). The roots and aerial parts showed the presence of varying abundance of different classes of phytochemicals such as total phenolics, flavonoids, tannins, and saccharides.…”
Section: Discussionsupporting
confidence: 92%
“…Breit (PB). Among these herbs, the combination of ACD, ZR and GF also termed by Si-Ni decoction has shown proven efficacy for septic shock (Chen et al, 2011), sepsis (Brislinger et al, 2018;Zeng et al, 2019) by interfering with apoptosis and inflammatory responses (Aly et al, 2005;Endo et al, 2017;Yang et al, 2017;Endo et al, 2018;Bai et al, 2020). In the context of SI-NI decoction, the anti-inflammatory function has been emphasized by the addition of PGM (Jin et al, 2020), PB (Tian et al, 2020), SCF (Panossian & Wikman, 2008;Li et al, 2020;Li et al, 2021), PCW as well as CC (Csikos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…S1, Supplemental Table S1). These compounds have also demonstrated anti-inflammatory effects [19,20], therefore, it could be reasonably inferred that the anti-allergic inflammatory effects of the aqueous extract of BLAB may be the result of a combination of these antiinflammatory compounds, and more experiments will be needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizinic acid, a bioactive constituent of licorice root extract, is a potent inhibitor of 11-hydroxysteroid dehydrogenase and exhibits a range of corticosteroid-like activities [18]. Studies have shown that licorice exhibits many therapeutic effects, including anti-inflammatory, antioxidative, anti-allergenic, and antimicrobial properties [18][19][20]. Anise (Pimpinella anisum L.) seed is an important ingredient used in Chinese medicinal herbs.…”
Section: Introductionmentioning
confidence: 99%